Spatial Analysis of Air Pollution Dispersion from a Stationary Source through Wind Profile: Case Study in North Sumatra - Yosef Barita Sar Manik; Aisyah Bestari Siswohartono; Aulia Rizqi Aufa Rafiqi; Brilian Maulani Putri; Daffa Renaldhi Chaniago Mairuhu; Johanes Surya Utama Sede; Nati Nati (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2025)
The iron and steel industry constitutes one of the strategic pillars of economic development. However, it is also a major contributor to global air pollution due to high-temperature fossil fuel combustion inherent in its processes. This study aims to analyze the wind characteristics surrounding a steel and iron industrial facility in North Sumatra and to predict the areas most at risk from pollutant dispersion. Meteorological data from the NASA POWER Project database, covering the period from 2021 to 2024, were processed to examine local wind profiles across two distinct seasonal periods—rainy and dry. The analysis revealed that during the rainy season, winds predominantly originated from the northwest, with moderate speeds ranging from 2.10 to 3.60 m/s, leading to pollutant dispersion mainly toward the southeast (145°, 40%). Conversely, in the dry season, wind direction was more variable, as indicated by a low resultant vector percentage (11%), suggesting multidirectional pollutant spread. Across both seasons, the majority of wind speeds were below 2.10 m/s, which limits vertical atmospheric mixing and enhances pollutant retention near the surface. Air stagnation, particularly during transitional periods between seasons and under temperature inversion conditions, further intensifies pollutant accumulation. These findings underscore the critical role of seasonal wind dynamics in air pollution behavior and provide a scientific foundation for developing effective mitigation strategies. Practical policy implications include the establishment of buffer zones in downwind residential or agricultural areas, the implementation of stricter emission controls during periods of low wind speed and stagnation, and the integration of local wind data into early warning systems for air quality. Such measures are essential to protect public health, especially in high-density areas surrounding PT X, including Medan City, Deli Serdang Regency, Serdang Bedagai Regency, and Tebing Tinggi City.